2020
DOI: 10.3390/su13010291
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Policy and the Legislative Context of the Water and Wastewater Sector in South Africa

Abstract: The water and wastewater sector is an important lifeline upon which other economic sectors depend. Securing the sector’s critical infrastructure is therefore important for any country’s economy. Like many other nations, South Africa has an overarching national cybersecurity strategy aimed at addressing cyber terrorism, cybercriminal activities, cyber vandalism, and cyber sabotage. The aim of this study is to contextualise the water and wastewater sector’s cybersecurity responsibilities within the national cybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Water and wastewater treatment is an important lifeline for the economic development of any country, and it is very important to secure these sectors. Malatji et al has provided a report on South Africa's cybersecurity strategy aimed at addressing cyber terrorism and cybercriminal activities [20]. In this study, they found that along with the National Cybersecurity Policy Framework, the Electronic Communications and Transactions Act, Critical Infrastructure Protection Act, and other supporting legislation, a wastewater sector's computer security incident response team can be established without the need to propose any new laws or amend existing ones.…”
mentioning
confidence: 89%
“…Water and wastewater treatment is an important lifeline for the economic development of any country, and it is very important to secure these sectors. Malatji et al has provided a report on South Africa's cybersecurity strategy aimed at addressing cyber terrorism and cybercriminal activities [20]. In this study, they found that along with the National Cybersecurity Policy Framework, the Electronic Communications and Transactions Act, Critical Infrastructure Protection Act, and other supporting legislation, a wastewater sector's computer security incident response team can be established without the need to propose any new laws or amend existing ones.…”
mentioning
confidence: 89%
“…As an instance, the USA has really developed comprehensive policies including Cybersecurity Improvement Act and Cybersecurity Details Sharing Act, which want to improve cybersecurity treatments and help in details sharing in between public and private sectors Shandler et al (2021). On the contrary, countries like South Africa and United Arab Emirates have really accomplished good operations to avoid cybercrimes & cyberattacks (Malatji & Solms, 2020;Younies & Tawil, 2020). Global nature of cyber hazards better intensifies enforcement difficulties, as collaboration amongst many territories is typically called for.…”
Section: National Approaches To Cyber Terrorism and Their Internation...mentioning
confidence: 99%
“…This circumstance reveals the significance of readiness and durability in lowering the impact of the cyber assaults. It additionally highlights the requirement for trustworthy synchronization between federal authorities' firms, economic sector bodies, and global partners in responding towards cyber terrorism (Malatji & Solms, 2020). Eventually, the worldwide involvement and collaboration are critical for taking care of the proceeding hazard of cyber violence.…”
Section: Case Study Analysis Of National Responses To Cyber Terrorismmentioning
confidence: 99%
“…Prior to the occurrence of a significant security attack or during active cybersecurity incident investigation, having the necessary information sharing strategy in place and effectively executing such strategy is very important for ensuring that all parties are kept informed in the prior, during, and post stages of any given cybersecurity incident handling [65], [66], [67], [64], [68], [69]. "Information about threats can improve an organization's situational awareness, expand its understanding of the current threat horizon and increase its defensive agility by improving decision making" [64].…”
Section: ) Information Sharingmentioning
confidence: 99%